An in vitro model to assess effects of a desensitising agent on bacterial biofilm formation. Issue 1 (2nd January 2019) - Coulter, Jamie; Jakubovics, Nicholas S.; Preshaw, Philip M.; German, Matthew J.
Abstract: Desensitising agents are added to dentifrices to occlude exposed dentine tubules and reduce pain associated with dentine hypersensitivity. In occluding the tubules these agents may alter the surface layer of the dentine and consequently affect bacterial biofilm formation. This research sought to examine the effects of desensitising agents on dentinal biofilms using an in vitro model. A constant depth film fermenter (CDFF) was selected to mimic the oral environment and human dentine with exposed tubules was analysed. Calcium sodium phosphosilicate (CSPS) was selected as a model desensitising agent. Dentine discs were treated with pumice or CSPS-containing dentifrices with or without fluoride, or left untreated (control). Dual-species biofilms of Streptococcus mutans and Streptococcus sobrinus were grown in artificial saliva and analysed by viable counts, polymerase chain reaction (PCR) and scanning electron microscopy (SEM). SEM images confirmed the presence of occluded tubules after CSPS application and demonstrated the formation of biofilms containing extracellular matrix material. Analysis of PCR and viable count data using a one-way ANOVA showed no significant differences for bacterial composition for any of the four treatments. There were, however, trends towards increased numbers of bacteria for the pumice and CSPS treated samples which was reversed by the addition of fluoride to CSPS. In conclusion, CSPS was not found to have a significant effect on biofilms and an in vitro model for testing desensitising agents has been developed, however, further work is required to improve the reproducibility of the biofilms formed and to explore the trends seen.